Some Remarks on the Tradition of the “„Viennese School of International Law” in the Context of its Historical Evolution - Lech, Marcin (Polish Review of International and European Law, 2023)
The article is based on some remarks on the tradition of the socalled Viennese School of International Law analysed by its main historical evolution stages from the beginning until today. The Viennese School is presently the one of the world’s oldest professional schools in international law. It was and it is represented by highly reputable scholars having outstanding achievements. Their determination of teaching, research, including an excellent publication record and international reputation has a special focus on multidisciplinarity. All of this builds a main parameters of this School. The sources of research are fields related to legal sciences, especially of history of teaching and research of international law in Vienna, international relations, sociology and, above all, philosophy. Thus, the above mentioned School has been valued in the world by many scholars of different schools. The community combining contemporary and modern lawyers, followers and supporters of the Viennese School of International Law, has never have the same interests or common beliefs. However, they share a common method of theoretical thinking and methodological approaches of the Viennese School in the field of international law. Therefore, today the main task of dealing with the objective of the Viennese School of International Law is primarily striving to understand international law as a separate kind of normative order in an multidisciplinary context.